STRUKTUR CORPORATE GOVERNANCE DAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN: STUDI PADA PERUSAHAAN JASA DI BEI - Tri Gunarsih; Bambang Hartadi (Jurnal Keuangan dan Perbankan, 2008)
The main objective of this study was to examine the impact of corporate governancestructure and the performance of the firms to timeliness in Indonesian Stock Exchange. Thisstudy combined corporate governance structure and timeliness study. Samples in this studywere service public companies. The research questions were tested by running two logisticsregression models. The dependent variables were dyygre timeliness proxied by dummy variable.It got 1 if companies published financial report before 120 days after December 31st and itgot 0 if the report was published after 120 days after December 31st. Governance structureswere proxied by ownership concentration and number of the Board of Directors and numberof the Board of Commissioners. Ownerships concentration was measured by herfindahl indexdomestic institution (HI_DOM). HI_DOM was the sum of square of ownership proportion bydomestic institution. The result of this study showed that there was a negative relationshipbetween number of the Board of Directors (as one of governance structure proxy) andtimeliness. The other significant variable was ROI as financial performance proxy.